Serum lactate dehydrogenase in the prognostic assessment of patients with oral squamous cell carcinoma - Jimson Sudha; Amaladas Julius; Samson Jimson; Kesavaram Padmavathy (Wolters Kluwer Medknow Publications, 2022)
Background: Lactate dehydrogenase (LDH) has been proven to be a diagnostic marker in oral squamous cell carcinoma (OSCC). However, the prognostic value of serum LDH in OSCC is yet to be explored. The purpose of this study is to correlate the level of serum LDH with the degree of OSCC and to evaluate the role of serum LDH as a prognostic marker in OSCC. Methods: The investigators designed and implemented a prospective cohort study composed of patients with OSCC (n = 66) sub-grouped as follows: 2A-well-differentiated (n = 22), 2B-moderately differentiated (n = 22), 2C-poorly differentiated OSCC (n = 22), and normal healthy controls (n = 40). The primary outcome variable was the serum LDH measured at baseline (pre-treatment) and 2 and 12 months post-treatment in OSCC patients. The statistical analysis was performed using the student t-test and analysis of variance, and the P value was set at 0.05. Results: The habit of alcohol consumption alone as a single habit was found only in males (17.5%) (P = 0.3343), whereas betel quid chewing was more common among females (P = 0.0182). A significant difference was observed in the mean serum LDH between OSCC subjects (pre-treatment) (831.56 ± 93.43 IU/L) and controls (188.82 ± 25.53 IU/L), P < 0.00001. The baseline serum LDH was significantly higher in subgroup 2C (933.41 ± 46.1969 IU/L) than in the 2A (742.59 ± 46.5676 IU/L) and 2B (818.68 ± 58.1643 IU/L) subgroups (P = 0). There was a significant decline in the serum LDH within 2 months after treatment, and a further decrement was observed during a 12-month follow-up among the survivors of all three subgroups; P < 0.00001. Conclusion: Serum LDH can play a dual role as a reliable indicator of the degree of OSCC for decision-making in treatment modalities and as a prognostic marker of response to therapy.